Impact Assessment of Export Processing Zones on Exportation of Cashew Nuts: The Way Forward for Sustainable Development in Nigeria - Chinedum , Obikeze O.; Ifeoma , Ifejika H. (African Journal of Education,Science and Technology (AJEST), 2017)
This study concentrated on assessing the impact of the export processing zones on exportation of cashew nuts in Nigeria. The export zones and cashew nuts exporters who are investors in the zones are facing a lot of challenges including poor implementation of incentives (tax holiday, free export and import licenses), poor infrastructural facilities (processing plants, water, power supply), and bad roads which resulted to waste of tones of cashew nuts. Strong attempt was made to find out the contribution of cashew nuts exports revenue to the country’s GDP. Four hypotheses were formulated from research questions which were in line with the objectives of the study. Using survey design, it was found that eleven (11) out of twenty-four (24) exports processing zones are operational in Nigeria, there is very low implementation of incentives by Export Processing zones, poor infrastructural facilities scare away investors irrespective of cashew nuts export significant contributions to Nigeria Gross Domestic Product (GDP). Export Processing zones, Authority should therefore sit up to their obligations: motivating the investors, and Nigerian government should adequately repair all roads to cash nuts farms, seaports and airports